Purification and Characterization of α-L-rhamnosidase from Bacillus amyloliquefaciens –D1 - Pegu, Bhaba Kumar; Kardong, Devid; Gogoi, Dip Kumar (Asian Journal of Biological and Life Sciences)
Rhamnosidase enzyme important role in debittering technology of citrus fruit juices. The other industrial sector considered a potential user of wine enhancement, antibiotic preparation, preparation of rhamnose, prunin and hydrolysis of glycoside. The enzyme rhamnosidase enzyme isolated from in animals, plants, and microbial sources. The present study was attempted to purification and characterization of rhamnosidase enzyme from Bacillus amyloliquefaciens- D1.α-L- rhamnosidase enzyme which was extracted from the fermented broth of Bacillus amyloliquefaciens-D1 was purified about 3.08-fold with yield 35.77 by ammonium sulfate precipitation followed by Sephadex G-100 column chromatography. The purity of the enzyme was confirmed by High-performance chromatography and 12% SDS-PAGE indicate a single peak showed and molecular weight found 67kDa. The purified enzyme optimum pH and temperature were 6.0 and 40°C respectively. The effects of mental activity found showed that Fe2+ (131.4%) and NaCl (129.37%) were strong activators, while KCL and Cu2+ was a strong inhibitor of the rhamnosidase enzyme production. The enzyme kinetic constants Km and Vmax were 15.09 (mg/ml) and 2.22 (mg/ ml/min), respectively. Further exploitation of the strain in large scale field application will help in citrus processing and bioprocess industries.
Keywords: Ammonium sulfate; Bacillus amyloliquefaciens; Column chromatography; HPLC; rhamnosidase; SDS-PAGE